Rare connective tissue diseases in patients with C1-inhibitor deficiency hereditary angioedema: first evidence on prevalence and distribution from a large Italian cohort study - Triggianese, P.; Senter, R.; Perego, F.; Gidaro, A.; Petraroli, A.; Arcoleo, F.; Brussino, L.; Giardino, F.; Rossi, O.; Bignardi, D.; Quattrocchi, P.; Brancaccio, R.; et al. (Frontiers in Immunology, 2024)
In patients with Hereditary Angioedema (HAE) related to primary C1 inhibitor deficiency (C1INH), the defective clearance of immune complexes and apoptotic materials along with impairment of normal humoral response potentially leads to autoimmunity. Few studies report evidence on autoimmune diseases in C1INH-HAE, but no large population studies focus on rare connective tissue diseases (RCTDs). We aim at evaluating for the first time prevalence and distribution of RCTDs -Systemic Lupus Erytematosus (SLE), primary Sjogren Syndrome (SjS), primary antiphospholipid syndrome (APS), Systemic Sclerosis (SSc), and mixed connective tissue diseases (MCTD) in a large Italian cohort of C1INH-HAE patients.. A multicenter observational study includes C1INH-HAE patients from ITACA Centers throughout Italy (time frame Sept 2023-March 2024). Inclusion criteria are i. a defined diagnosis of type I or type II C1INH-HAE; ii. age ≥15 years (puberty already occurred); iii. enrollment in the ITACA Registry. The diagnosis of SLE, primary SjS, primary APS, SSc, and MCTD are made in accordance with international classification criteria.Results. Data are collected from a total of 855 C1INH-HAE patients referring to 15 ITACA Centers.Patients with concomitant RCTDs were 18/855 (2.1%) with F:M ratio 3.5 and a prevalent type I C1INH-HAE diagnosis (87.2%). A diagnosis of SLE results in 44.5% of cases (n=8) while the remaining diagnoses are primary SjS (22.2%, n=4), primary APS (16.6%, n=3), SSc (11.2%, n=2), and a single case of MCTD (5.5%). The female gender is prevalent in all the RCTDs. Patients on long term prophylaxis (LTP) are significantly prevalent in RCTDs group than in the whole C1INH-HAE population (p<0.01).